2022
DOI: 10.54093/bmra.v1i1.2123
|View full text |Cite
|
Sign up to set email alerts
|

Employee Motivation, Job Reengineering, and Perceived Job Satisfaction: A Quantitative Correlational Approach

Abstract: This quantitative research investigated the correlation between employee motivation, job reengineering, and the perception of job satisfaction among the civilian employees of the Department of Defense located in Washington, D.C., United States. The theoretical foundation for the study was rooted in Deci and Ryan's (1985; 2000) self-determination theory of motivation. The researcher utilized a non-experimental correlational research design and an appropriate non-probability convenience sampling method to collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 83 publications
(175 reference statements)
0
1
0
Order By: Relevance
“…Hasibuan (2016) states that Motivation is an encouragement that can influence employees to work together effectively to achieve goals. Research by Martin & Goldwasser (2022) found that providing autonomy, opportunities to master new skills, and meaningful goals can increase employee motivation and performance. Various motivation theories explain the factors that influence motivation, such as basic human needs, rewards, recognition, and opportunities for growth.…”
Section: Introductionmentioning
confidence: 99%
“…Hasibuan (2016) states that Motivation is an encouragement that can influence employees to work together effectively to achieve goals. Research by Martin & Goldwasser (2022) found that providing autonomy, opportunities to master new skills, and meaningful goals can increase employee motivation and performance. Various motivation theories explain the factors that influence motivation, such as basic human needs, rewards, recognition, and opportunities for growth.…”
Section: Introductionmentioning
confidence: 99%